2014
DOI: 10.1002/eji.201343781
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response induces antigen presenting cell‐like functions in fibroblasts

Abstract: Keywords: Adaptive immunity r Antigen-presenting cell r Chemotherapy r DNA damage r Fibroblasts Additional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…36 Data from several other reports have revealed that the DNA damage responses mediated by ATR, ATM and CHEK1 may alert the immune system to the presence of potentially dangerous cells by upregulating the expression of ligands that can induce the activation of innate and adaptive immune cells. 37,38 Our current study provides novel evidence for a critical role of the ATR-CHEK1 axis activation in mediating the proinflammatory response in bronchial epithelial cells under PM2.5 exposure (Figs. 6 to 8), further confirming the functional link between checkpoint pathways and immune responses under particle-induced stress.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…36 Data from several other reports have revealed that the DNA damage responses mediated by ATR, ATM and CHEK1 may alert the immune system to the presence of potentially dangerous cells by upregulating the expression of ligands that can induce the activation of innate and adaptive immune cells. 37,38 Our current study provides novel evidence for a critical role of the ATR-CHEK1 axis activation in mediating the proinflammatory response in bronchial epithelial cells under PM2.5 exposure (Figs. 6 to 8), further confirming the functional link between checkpoint pathways and immune responses under particle-induced stress.…”
Section: Discussionmentioning
confidence: 65%
“…26,27 In the light of recent studies, functional links between the immune response and the ATR-CHEK1-mediated processes that regulate genomic integrity have also been revealed. [35][36][37][38] For example, the ATR-CHEK1 pathway was found to be activated in the Simian virus 40 large T antigen-induced DNA damage response in human fibroblasts, resulting in the induction of IRF1 (interferon regulatory factor 1) and the transactivation of IFNB1 (interferon b 1) to mediate the antiviral response. 35 Intriguingly, in germinal center B cells, downregulation of the ATR-CHEK1 checkpoint axis is required for efficient somatic hypermutation and IgG diversification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to altering the extrinsic immunogenicity of tumors at the level of the microenvironment, DNA damage can also alter the intrinsic immunogenicity of tumor cells through modulation of surface phenotype. For example, studies of aphidicolin and cytarabine have shown the ability of DNA-damaging agents to drive upregulation of natural-killer group 2, member D ligands, inducible T-cell costimulator (ICOS) ligand and MHC class I, in an ATM-or ATR-dependent manner (76,77). These studies, though not directly related to PARP inhibition, suggest that increased DNA damage can make cells more visible to, and sensitive to killing by, T cells and natural killer (NK) cells, through modulation of surface phenotype.…”
Section: Fundamental Links Between Dna Damage Inflammation Cancer Pmentioning
confidence: 99%
“…The rationale for this combination is that inhibition of PARP will result in an increase in mutational load and modification of tumor immunogenicity, 59 , 60 resulting in an increased sensitivity to immune checkpoint inhibitors of CTLA-4, programmed cell death-1, and programmed cell death-ligand 1 (PD-L1). This is supported by preclinical data, but we are yet to see the final results of the current studies.…”
Section: Future Directions and Challenges For Rucaparib And The Classmentioning
confidence: 99%